Elevated CO2 Reduced Floret Death in Wheat Under Warmer Average Temperatures and Terminal Drought - Dias de Oliveira, Eduardo; Palta, Jairo A.; Bramley, Helen; Stefanova, Katia; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2015)
Elevated CO2 often increases grain yield in wheat by enhancing grain number per ear, which can result from an increase in the potential number of florets or a reduction in the death of developed florets. The hypotheses that elevated CO2 reduces floret death rather than increases floret development, and that grain size in a genotype with more grains per unit area is limited by the rate of grain filling, were tested in a pair of sister lines contrasting in tillering capacity (restricted- vs. free-tillering). The hypotheses were tested under elevated CO2, combined with +3°C above ambient temperature and terminal drought, using specialized field tunnel houses. Elevated CO2 increased net leaf photosynthetic rates and likely the availability of carbon assimilates, which significantly reduced the rates of floret death and increased the potential number of grains at anthesis in both sister lines by an average of 42%. The restricted-tillering line had faster grain-filling rates than the free-tillering line because the free-tillering line had more grains to fill. Furthermore, grain-filling rates were faster under elevated CO2 and +3°C above ambient. Terminal drought reduced grain yield in both lines by 19%. Elevated CO2 alone increased the potential number of grains, but a trade-off in yield components limited grain yield in the free-tillering line. This emphasizes the need for breeding cultivars with a greater potential number of florets, since this was not affected by the predicted future climate variables.